Cutaneous adverse events to systemic antineoplastic therapies: a retrospective study in a public oncologic hospital - William Queiroz Guimarães Wiegandt Ceglio; Marina Mattos Rebeis; Marcela Ferreira Santana; Denis Miyashiro; Jade Cury-Martins; José Antônio Sanches (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Mucocutaneous adverse events are common during anticancer treatment, with variable consequences for the patient and their therapeutic regimen. Objective: To evaluate the most common adverse events, as well as the drugs associated with their appearance and the consequences for cancer treatment. Methods: A retrospective study was carried out through the analysis of patients treated at the Clinical Dermatology Unit of a public oncologic hospital. Results: A total of 138 patients with 200 adverse events were evaluated. The most commonly identified adverse events were nail and periungual changes (20%), papulopustular eruptions (13%), acneiform eruptions (12%), hand-foot syndrome (6.5%), hand-foot skin reaction (6%), and xerosis (6%). The most frequently associated antineoplastic treatment groups were classical chemotherapy (46.2%), target therapy (32.3%), and other non-antineoplastic drugs used in neoplasia protocols (16.5%). Of the total number of patients, 17.4% had their treatment suspended or changed due to a dermatological adverse event. Study limitations: Retrospective study and analysis of patients who were referred for specialized dermatological examination only, not allowing the assessment of the actual incidence of adverse events. Conclusion: A wide variety of dermatological manifestations are secondary to antineoplastic treatment with several different drugs resulting, not rarely, in the interruption or modification of therapeutic regimens.